1995
DOI: 10.1016/0014-5793(95)01134-z
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of endothelial nitric oxide synthase expression by cyclic guanosine 3′,5′‐monophosphate

Abstract: In this study, the role of cyclic GMP, the end product of the NO-cyclic GMP signalling pathway, in the regulation of ecNOS was investigated. Bovine pulmonary endothelial cells were exposed to 8-bromo-cyclic GMP and its effect on NO production, ecNOS protein, and mRNA levels was analyzed. Endothelial cells on exposure to 8-bromo-cyclic GMP produced significantly increased amounts of NO, detected as increased cyclic GMP in cocultures with vascular smooth muscle cells both under basal conditions and with agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In bovine main pulmonary artery endothelium, eNOS expression is increased by exogenous cGMP, and a cGMP-dependent positive-feedback control of eNOS has been proposed. 44 Our results show that increased eNOS expression was paralleled by reduced intracellular cGMP levels. We hypothesize that eNOS gene expression could be regulated by a negative-, rather than a positive-, feedback control mechanism in HUVECs.…”
Section: Casanello Et Al Iugr Inhibits Endothelial L-arginine/no Pathwaysupporting
confidence: 53%
“…In bovine main pulmonary artery endothelium, eNOS expression is increased by exogenous cGMP, and a cGMP-dependent positive-feedback control of eNOS has been proposed. 44 Our results show that increased eNOS expression was paralleled by reduced intracellular cGMP levels. We hypothesize that eNOS gene expression could be regulated by a negative-, rather than a positive-, feedback control mechanism in HUVECs.…”
Section: Casanello Et Al Iugr Inhibits Endothelial L-arginine/no Pathwaysupporting
confidence: 53%
“…[38][39][40] Certainly, Yamamoto et al 38 and Marumo et al 39 showed that activation of cGMP-protein kinase by ANP via cGMP upregulates cytokine-induced iNOS expression after 24-hour incubation in the cells mentioned above. However, on the basis of the present results, this mechanism should be ruled out, because de novo synthesis of the enzyme is unlikely to occur within this brief experimental period.…”
Section: Table 3 Effects Of Anp On Nadph-d Activitymentioning
confidence: 99%
“…20 Furthermore, an upregulated eNOS was found in cultured endothelial cells incubated for 48 hours with 8-bromocGMP. 21 Another candidate that contributes to the upregulation of eNOS expression induced by endogenous kinins might be cAMP. Increased endothelial cAMP is induced by forskolin and amplified by activation of a cAMP-dependent protein kinase, the bradykinin-induced synthesis of cGMP.…”
mentioning
confidence: 99%